2017
DOI: 10.1088/1361-6560/aa86ea
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Radiation DOSimetry phantom (ARDOS): a versatile breathing phantom for 4D radiation therapy and medical imaging

Abstract: A novel breathing phantom was designed for being used in conventional and ion-beam radiotherapy as well as for medical imaging. Accurate dose delivery and patient safety are aimed to be verified for four-dimensional (4D) treatment techniques compensating for breathing-induced tumor motion. The phantom includes anthropomorphic components representing an average human thorax. It consists of real tissue equivalent materials to fulfill the requirements for dosimetric experiments and imaging purposes. The different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…End-to-end tests are particularly useful for multi-centre audits (Clark et al 2015, Lambrecht et al 2019, Wesolowska et al 2019) and have shown that they are useful for comparing the magnitude of dose differences due to effects such as motion (de Jong et al 2017, Kostiukhina et al 2017, Perrin et al 2017, Pallotta et al 2018, Ehrbar et al 2019 or magnetic fields (Steinmann et al 2019a(Steinmann et al , 2020, see table 6. Reported absolute differences can be variable depending on the dosimeter employed (Kostiukhina et al 2017), although it may be challenging to disassociate errors due the treatment planning system, treatment delivery, detector limitations or the material characteristics. Careful characterization of the material properties can allow explanation of the uncertainties associated with this component of any overall differences observed (Taylor et al 2016, Steinmann et al 2018.…”
Section: Review Of Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…End-to-end tests are particularly useful for multi-centre audits (Clark et al 2015, Lambrecht et al 2019, Wesolowska et al 2019) and have shown that they are useful for comparing the magnitude of dose differences due to effects such as motion (de Jong et al 2017, Kostiukhina et al 2017, Perrin et al 2017, Pallotta et al 2018, Ehrbar et al 2019 or magnetic fields (Steinmann et al 2019a(Steinmann et al , 2020, see table 6. Reported absolute differences can be variable depending on the dosimeter employed (Kostiukhina et al 2017), although it may be challenging to disassociate errors due the treatment planning system, treatment delivery, detector limitations or the material characteristics. Careful characterization of the material properties can allow explanation of the uncertainties associated with this component of any overall differences observed (Taylor et al 2016, Steinmann et al 2018.…”
Section: Review Of Materialsmentioning
confidence: 99%
“…Steidl et al 2012 developed a series of specifications for dynamic radiotherapy phantoms, one of which was to include inhomogeneities such as rib structures. Many dynamic lung phantoms have been developed with inhomogeneities(Mann et al 2017, Pallotta et al 2018, Kostiukhina et al 2017, Perrin et al 2017 …”
mentioning
confidence: 99%
“…An independent tumor motion in all three directions as well as a thorax movement can be facilitated on the basis of arbitrary movement curves while inserts for films or ion chamber are available. Another sophisticated research phantom was developed at the Medical University of Vienna in cooperation with the Austrian Institute of Technology an Advanced Radiation DOSimetry phantom (ARDOS) in the frame of a Marie Curie project [59]. This phantom was built from three different tissue equivalent materials: high density balsa wood for lung, solid water for soft tissue and bone material.…”
Section: D Phantomsmentioning
confidence: 99%
“…To precisely analyze different imaging systems, a realistic phantom should accurately simulate a true patient scan including anatomy, tissue density and X-ray attenuation characteristics in the case of X-ray or computed tomography (CT) imaging. Tissue equivalency is not only relevant for image quality assessment but also for accurate radiation dosimetry especially for charged particles where the tissue composition influences the particle interactions (Kostiukhina et al, 2017;Kostiukhina et al, 2019). Despite the ubiquitous existence of various thoracic pathologies and their imaging-based surgical and diagnostic procedures, more realistic models are required (Nardi et al, 2017;Huang et al, 2019;Montigaud et al, 2019).…”
Section: Introductionmentioning
confidence: 99%